2018
DOI: 10.3390/f9020062
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Alters Initial Growth, Fine-Root Biomass and Soil Organic Matter Properties of a Eucalyptus dunnii Maiden Plantation in a Recently Afforested Grassland in Southern Brazil

Abstract: Nitrogen (N) fertilization effects on Eucalyptus growth and soil carbon (C) stocks are still controversial. We set up an N fertilization experiment in southern Brazil to evaluate initial tree growth and changes in soil organic matter (SOM). Four N levels (24-Reference, 36, 48 and 108 kg ha −1 of N) were tested and tree growth was assessed during the first two years. Afterwards, representative trees were chosen to evaluate fine-root biomass (FRB) and its spatial distribution. Soil was sampled to a 40-cm depth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…6 Comprehensive evaluation value of Populus deltoides genotypes under low nitrogen (LN 2 ), normal nitrogen levels (CK 2 ) and high nitrogen (HN 2 ) in the verification test. A-1, A-2 and A-3 represent the three N-efficient genotypes; C-1, C-2 and C-3 the three N-inefficient genotypes to biotic and abiotic stresses (Guo and Zhang 2010;Liu et al 2015;Zhao et al 2016a, b;Ferreira et al 2018;Ghezehei et al 2019;Zhang et al 2020). Kalcsits and Guy (2016) studied the variability of nitrogen uptake, assimilation and allocation traits of 25 Populus balsamifera L. genotypes from five climatically different provenances.…”
Section: Evaluation Of Plant Nitrogen Use Efficiencymentioning
confidence: 99%
“…6 Comprehensive evaluation value of Populus deltoides genotypes under low nitrogen (LN 2 ), normal nitrogen levels (CK 2 ) and high nitrogen (HN 2 ) in the verification test. A-1, A-2 and A-3 represent the three N-efficient genotypes; C-1, C-2 and C-3 the three N-inefficient genotypes to biotic and abiotic stresses (Guo and Zhang 2010;Liu et al 2015;Zhao et al 2016a, b;Ferreira et al 2018;Ghezehei et al 2019;Zhang et al 2020). Kalcsits and Guy (2016) studied the variability of nitrogen uptake, assimilation and allocation traits of 25 Populus balsamifera L. genotypes from five climatically different provenances.…”
Section: Evaluation Of Plant Nitrogen Use Efficiencymentioning
confidence: 99%
“…So, biogeochemical cycling of nutrients in dystrophic soils seems essential f or vegetation maintenance agains t leaching (DE SOUZA et al, 2018;LUCAS, 2001;MANZONI et al, 2010;SARCINELLI et al, 2013). The abundance of f ine and very f ine roots in soil prof ile reinf orces this hypothesis (FERREIRA et al, 2018;HASENMUELLER and SCOTT, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As litterfall, one of the main inputs of organic matter, was removed to control fires, we propose that increased SOC in the topsoil could be due to enhanced fine root turnover and changes in root distribution, which we did not measure. Fertilization in terrestrial ecosystems can increase the fine root turnover in poor soils (Yuan & Chen, 2012), especially in the topsoil (Ferreira et al, 2018; Wang et al, 2019) and a recent study in C. equisetifolia plantation also found that soil N availability was positively correlated with fine root biomass (Hu et al, 2017). In our study, changes in root turnover and distribution, rather than biomass, could enhance soil C inputs without a significant increase in R a .…”
Section: Discussionmentioning
confidence: 99%